La alucinante historia de Juanito Tot y Verónica Flut : (los niños que intentaron batir todos los records) - Barba, Andrés, 1975- (Tres edades, 2015)
Two friends, Juanito Tot and Verónica Flut, respond to an ad by Klaus Wintermorgen to set a world record in 30 days which the invincible Klaus cannot break.